A toolkit with nine district types to support municipalities in taking an integrated approach to prevention - Ilse Storm; Nikkie Post; Antonia Verweij; Karlijn Leenaars (BMC, 2019)
Abstract Background Not only do people differ in their health, so do districts within municipalities. For example, city centres have different characteristics and health issues than villages or post-war neighbourhoods. This is why the Dutch National Institute for Public Health and the Environment has developed a toolkit, 'Prevention in the district', based on nine different types of district. Methods The aim of the toolkit is to help municipalities implement an integrated approach to prevention by providing tailored, practical information. We therefore looked at the best way to improve the connection between the available knowledge and local needs. Based on data analysis, expert opinion and working sessions with professionals and local policymakers, we developed a toolkit with three related tools. Results The following tools were developed: 1) nine district types with their prominent characteristics and 14 themes for prevention (ranging from loneliness to overweight); 2) a data guide containing a set of indicators to assess the district health profile; 3) a prevention guide containing a mix of evidence-based interventions for the 14 themes. The tools are presented in a toolkit (a clickable PDF) to emphasise the fact that they form a coherent whole. The link between data and interventions is considered to be particularly innovative. Conclusion The three tools support the improvement of the health and well-being of residents in a district. The first indications are that the toolkit empowers municipalities and lets them work towards an integrated approach. An integrated approach in both district health profiles and district plans could also serve as an example for other countries.